Esencia de Mujer. Value proposition. Visual Identity - Albornoz Arias, Neida Coromoto; Rojas Sanguino, Camila Andrea; Santafé Rojas, Akever Karina (Sello Editorial Unipamplona, 2024)
This value proposition corresponds to the brand identity “Esencia de mujer” is the result of the research project: “Value proposition in the cocoa production unit(s) of rural women, to overcome the barriers they face along the production chain, through individual and collective empowerment, in the municipalities of Tibú and Sardinata, Colombia”. This project was funded by the Ministry of Science, Technology and Innovation (MINCIENCIAS) [Cod. 102882 CT 235-2023] Call for proposals 935. Women in Science: Agents for Peace, executed by the University of Pamplona. Esencia de Mujer is the insignia of the Association of Tibuyan Women Cocoa Growers of Catatumbo (Asociación de Mujeres Tibuyanas Cacaoteras del Catatumbo - ASOMUTICA). Esencia de Mujer is more than a flavour, it is a pact of trust that connects those who enjoy their cocoa with the vision of lasting tranquillity in lands that have flourished thanks to the effort and determination of its inhabitants. This document is structured as follows: introduction, corporate identity, logo and brand applications.